Anti Epileptic Activity of Morinda citrifolia Linn Fruit Extract - P. Muralidharan; J. Srikanth (E-Journal of Chemistry)
Fruit extract of Morinda citrifolia (Noni), a medicinal plant used in many neuro protective ayurvedic preparations was evaluated for its protective effect against seizures induced by Maximal Electro Shock (MES) method in rats. A daily dose of 200 and 400 mg/kg of the extract was administered to the animals for 15 days, after which seizures were induced by maximum electro shock method and the duration of various phases of epileptic attacks were recorded and compared with the control animals. A significant (P<0.01 and P<0.001) reduction in the time taken for righting reflex (recovery) was noted in the experimental animals. The levels of biogenic amines such as dopamine, serotonin and nor-adrenaline in the forebrain region were also estimated and a significant level of restoration was opserved in the extract treated animals. Significant results were opserved in the estimated parameters thereby justifying the use of this medicinal plant in the treatment of epilepsy.